Optimization of Spray Dryer Design for Small Scale Drying of Milk Using Computational Fluid Dynamics - Tamrakar, Ishan; Khadka, Jitendra; Baral, Bivek (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Spray drying technology has long been the industry standard for producing quality powdered products such as milk powder, coffee, juice powder, and pharmaceutical products. Spray dryers convert liquid or slurry directly into powdered form with the help of an atomizer and hot drying gas. One of the applications of such technology can be in the milk industry of Nepal. Spray drying of milk can increase the shelf life of milk and significantly reduce its volume, making it easy for storage and transport. This paper is concerned with the design of such a spray dryer for community-based applications. The drying chamber was designed based on previous literature on the topic. Then the analysis and refinement of the initial design were done using the ANSYS Fluent CFD package. An Eulerian-Eulerian framework was utilized to model the problem. The dimensions and thermo-physical properties were optimized for a drying capacity of 400 kg milk in 8 hours. The optimum inlet conditions were found to be 400 K, 0.385 kg/s for hot air inlet, and 318 K, 0.014 kg/s for milk inlet. The length and diameter of the dryer were optimized to 3700 mm and 1790 mm respectively. The airflow pattern at the axial region of the dryer was found to be downward directed, and that at the peripheral region was found to be turbulent with recirculating eddies. According to the observed trend in the transient simulation, the temperature of the milk reaches a value of 385 K at the inlet for a brief period of 0.78 s and then lowers to 365 K and eventually reaches 340 K while exiting the chamber after two seconds of injection. These results are improvements from previous industrial-scale spray dryers as the maximum temperature inside the dryer and the particle-residence-time were reduced. All of this leads to low thermal degradation of milk while drying.